Implementation outcomes of 1-3-7 focus investigation for malaria in a low transmission setting in Southern Province, Zambia: A mixed methods study. - Anne C Martin; Japhet Matoba; Caison Sing'anga; Mukuma Lubinda; Sydney Mweetwa; Xinyue Chen; Ignatius Banda; Busiku Hamainza; Harry Hamapumbu; Edgar Simulundu; William J Moss; Southern and Central Africa International Centers of Excellence for Malaria Research (PLOS Global Public Health)
Eleven countries have been certified as malaria free since 2016, but none of these are in subSaharan Africa where elimination challenges are unique. The 1-3-7 focus investigation approach is an implementation strategy that requires case reporting, case investigation/classification, and focal classification/response to be completed one, three, and seven days, respectively, after index case diagnosis. Real-time short-messaging-service reports are sent at each step to add accountability and data transparency. Reactive case detection is one focal response of the 1-3-7 strategy. China, Thailand, Myanmar, and other countries cite high fidelity to deadlines and broad acceptability of 1-3-7, but this strategy has yet to be widely deployed in Africa. This mixed-methods study evaluated implementation and service outcomes of 1-3-7 focus investigation in a rural area of southern Zambia. Selected outcomes were fidelity, efficiency, feasibility, equity, and acceptability, assessed via program metadata and semi-structured interviews with program personnel. Fidelity was moderate with 61% of cases reported. Focus investigation and reactive case detection completion doubled in areas using 1-3-7, from 20% to 42%. However, reactive case detection, which involved screening community members residing within 140 meter of index cases with a rapid diagnostic test, detected few parasitemic individuals, suggesting this may not be the most efficient day 7 response in this setting. Mobile phone network coverage was a common challenge to feasibility that likely affected reporting rates and fidelity. Thirty-four percent of health-facility diagnosed cases were not eligible for 1-3-7 follow-up. Distance from the health center was a barrier to feasibility and equitable reach of services. Reporting was faster in areas where health workers classified transmission as higher and slower in areas with poor mobile phone network coverage. The strategy was widely accepted. Scale-up should include adherence-focused management strategies, spatially targeted interventions not reliant on RDTs, and complementary surveillance that targets hard-to-reach populations.